PENINGKATAN KEAKTIFAN SISWA MELALUI TECHNOLOGICAL PEDAGOGIKCAL CONTENT KNOWLEDGE - Nuraisyiah Nuraisyiah; Abd Rijal; Sitti Hajerah Hasyim; Nurjannah Nurjannah; Fajriani Azis (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
Advances in the field of technology can be used as a way to increase active learning and the quality of learning that can be carried out by a teacher. The aim of the research is to increase student activity through TPACK. The research method used is a qualitative descriptive method. TPACK at SMKN 7 Takalar has generally been implemented in learning but is still not 100% optimal due to several obstacles including: teachers' lack of mastery over media, limited availability of LCDs, insufficient internet access/quota and restrictions on cell phone operation during learning hours. The limitation is intended because there is still a small portion of students who do not use cellphones/internet wisely during learning hours.